Pengaruh Kompensasi dan Motivasi terhadap Kinerja Karyawan (Studi Kasus pada Karyawan PT Dipa Pharmalab Internsains Jakarta) - Fransisca Marseilla (EXERO : Journal of Research in Business and Economics, 2020)
The aim of this research is to find out the influence of compensation and motivation on work performance of the employees of PT DIPA Pharmalab Intersains Jakarta. The population of this research is the employees of PT DIPA Pharmalab Intersains Jakarta and the sample consists of 100 respondents. The sampling technique used in this research is purposive sampling. The data collection technique includes interview and self-report questionnaire. The data is analyzed by using statistical techniques including multiple linear regression, F-test, T-test and determinant coefficient. The result of the analysis suggests that simultaneously compensation and motivation influence the employees’ work performance. Partially, motivation influences the employees’ work performance, and whereas compensation does not.